Sejarah Perbandingan Sistem Pendidikan Denmark dengan Sistem Pendidikan Indonesia - Ayu Firdaus; Mislaini Mislaini; Imal Latul Khaira (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2025)
This study aims to understand the education system in Denmark, compare it with the education system in Indonesia, and identify positive aspects that can be adopted for the development of the education system in Indonesia. This study was conducted through a literature approach using critical, dialectical, and scholastic methods. Relevant data and theories were obtained from various literatures, then analyzed in depth. The results of the study indicate that the education system in Denmark is based on socio-cultural values ​​such as freedom of speech, self-control, equality, and mutual trust and respect. In addition, education in Denmark has many positive aspects that support the development of students, both in academic and non-academic aspects, with the positive aspects being much more dominant than the negative aspects. These findings indicate that the Danish education system offers various inspirations that can be adapted to improve the quality of education in Indonesia.